Fitting single-walled carbon nanotube optical spectra - Pfohl, Moritz; Graf, Arko; Zaumseil, Jana (ACS omega, 2017)
In this work, a comprehensive methodology for the fitting of single-walled carbon nanotube absorption spectra is presented. Different approaches to background subtraction, choice of line profile, and calculation of full width at half-maximum are discussed both in the context of previous literature and the contemporary understanding of carbon nanotube photophysics. The fitting is improved by the inclusion of exciton-phonon sidebands, and new techniques to improve the individualization of overlapped nanotube spectra by exploiting correlations between the first- and second-order optical transitions and the exciton-phonon sidebands are presented. Consideration of metallic nanotubes allows an analysis of the metallic/semiconducting content, and a process of constraining the fit of highly congested spectra of carbon nanotube solid films according to the spectral weights of each (n, m) species in solution is also presented, allowing for more reliable resolution of overlapping peaks into single (n, m) species contributions.